CEA-delta could be a biomarker of tumor phenotype, clinical stage, and chemotherapeutic response in rectal cancer with OCT4-positive cancer stem cells - Lozada-Martinez, Ivan David; Bolaño-Romero, Maria Paz; Lambis-Anaya, Lina; Liscano, Yamil; Suarez-Causado, Amileth (Frontiers in Oncology, 2023)
Background: There is very limited evidence on biomarkers for evaluating the clinical behavior and therapeutic response in rectal cancer (RC) with positive expression of cancer stem cells (CSCs). Methods: An exploratory prospective study was conducted, which included fresh samples of tumor tissue from 109 patients diagnosed with primary RC. Sociodemographic, pathological and clinical characteristics were collected from medical records and survey. The OCT4 protein was isolated using the Western Blot technique. It was calculated the ΔCEA, ΔOCT4, and ΔOCT4/GUSB values by assessing the changes before and after chemotherapy, aiming to evaluate the therapeutic response. Results: Patients had an average age of 69.9 years, with 55% (n=60) being male. Approximately 63.3% of the tumors were undifferentiated, and the most frequent staging classification was pathological stage III (n=64; 58.7%). Initial positive expression was observed in 77.1% of the patients (n=84), and the median ΔCEA was -1.03 (-3.82 - 0.84) ng/ml, with elevated levels (< -0.94 ng/ml) found in 51.4% of the subjects (n=56). Being OCT4 positive and having an elevated ΔCEA value were significantly associated with undifferentiated tumor phenotype (p=0.002), advanced tumor progression stage (p <0.001), and negative values of ΔOCT4 (p <0.001) (suggestive of poor therapeutic response) compared to those without this status. Conclusions: This study identified a significant and directly proportional association among the values of ΔCEA, ΔOCT4, and ΔOCT4/GUSB. These findings suggest that ΔCEA holds potential as a clinical biomarker for determining the undifferentiated tumor phenotype, advanced clinical stage, and poor therapeutic response in RC with CSCs positive expression.